ANALISIS CEMARAN BAKTERIOLOGIS DAN LOGAM BERAT DAGING LANGKITANG (Faunus ater) (Universitas PGRI Sumatera Barat, 2020)
As a popular food ingredient, meat langkitang consumed must be protected from contamination of pathogenic microbes and heavy metals that can interfere with and endanger human health. This study aims to determine the level of bacteriological contamination and heavy metal meat langkitang (Faunus ater). meat Langkitang was taken as many as 15 samples randomly, obtained from traders around the coast of Padang, West Sumatra. Examination of microbial contamination in meat used a method (serial dilution) Most Probable Number (MPN) consisting of the presumptive test, confirmed test and completed test. Measurement of Lead Heavy Metal (Pb) content was carried out by measuring the absorption value of the meat used a Atomic Absorption Spectrophotometry (AAS). The results of bacteriological analysis showed that all samples of tested meat tested positive contained contaminating bacteria. Test of heavy metals shows that contamination of meat from meat langkitang (Faunus ater) has exceeded the threshold. This study concludes that bacteriological and heavy metal analysis shows that contamination of microbial and Lead metal (Pb) in langkitang meat that has exceeded the health threshold so that proper processing is needed before meat is consumed.